(untitled) (Jurnal Rekayasa Mesin dan Inovasi Teknologi, 2021)
HighLight B5 + or what is generally called a tower lamp is a support tool that is usually used as a source of lighting during nighttime activities in a coal mine, and the HighLight B5 + is the latest generation of tower lamps where the hydraulic system is used as a driver of tower poles. lamp, in the hydraulic system of this unit the gear pump is a major component used and in general the longer the operating life of the gear pump will experience a decrease in performance. From the problem of the decline in the performance of the gear pump on the HighLight B5 + unit, I am interested in conducting a comparative analysis of performance and the purpose of this study is to determine the extent of the decline in the performance of the hydraulic pump with the gear pump type of HighLight B5 + Atlas Copco after operating for 11,000 hours and provide information hydraulic system which has now been applied to the tower lamp unit. The method used is quantitative by providing information about the performance of the gear pump on the HighLight B5 + Atlas Copco unit, where the independent variable is the life time of the gear pump 11,000 hours and the data collection process is carried out at the workshop of PT. Inti Raya Anugrahtama by conducting literature studies to find out the basic theory, working principles and other supporting literature regarding the gear pump, observing data by making direct observations in the field in order to get more concrete data. The results of the analysis and discussion on the research of new gear pumps and those that have been operating for 11,000 hours show that the performance difference from the pressure of each gear pump is 1.45 Psi / s and the average flow pressure is 0.1 Ltr / s.